2015
DOI: 10.1001/jamaophthalmol.2014.3869
|View full text |Cite
|
Sign up to set email alerts
|

Accidental Subretinal Brilliant Blue G Migration During Internal Limiting Membrane Peeling Surgery

Abstract: rilliant blue G (BBG) selectively stains the internal limiting membrane (ILM), improving visualization during ILM peeling. 1 Despite controversy about the safety profile of the dye, BBG has been widely used intraoperatively in many countries. 1 Accidental delivery of dyes into the subretinal space is a well-known complication associated with macular surgical procedures. 2-5 In this report, we describe the outcomes of retinal function and structure during 2 years in a patient after epiretinal membrane (ERM) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…This may, therefore, lead to increased surgical risk. Some studies have shown that dye injection might result in migration of the dye into the subretinal space [ 20 ]. In our study, this complication occurred in two eyes (4%).…”
Section: Discussionmentioning
confidence: 99%
“…This may, therefore, lead to increased surgical risk. Some studies have shown that dye injection might result in migration of the dye into the subretinal space [ 20 ]. In our study, this complication occurred in two eyes (4%).…”
Section: Discussionmentioning
confidence: 99%
“…BBG, it was claimed, provided a good staining to the ILM and was not toxic in experimental studies and a case series in humans [ 15 ]. However, recent reports showed a selective toxicity to photoreceptors related to BBG after intravitreal injection in rabbit eyes and RPE changes on fluorescein angiography, as well as macular damage following accidental subretinal dye injection in humans [ 16 20 ]. Another report of the intraocular safety of ICG, TB, Evans blue (EB), and BBG on ARPE-19 cell lines and murine retinal ganglion/Müller glial (RGC) primary cell cultures showed that all dyes demonstrated relatively safe viability profiles in both cell lines at surgically relevant concentrations and times.…”
Section: Introductionmentioning
confidence: 99%
“…The ideal dye for vitreoretinal surgery should be a high grade of purity compound, in order to avoid any potential interference during surgery. It has been reported that retinal damage can occur after treatment with vital dyes, and this is linked to the passive absorption of molecules in the retinal layers underneath the ILM (Kanda et al, 2004;Kawahara et al, 2007;Ueno et al, 2007;Maia et al, 2009;Ejstrup et al, 2012;Savary and Kodjikian, 2014;Almeida et al, 2015;Hurst et al, 2017) (Figure 1). On the basis of predicted ADME properties of PBB ® the risk of iatrogenic retinal damage is very low, also due to poor absorption into the retina.…”
Section: Discussionmentioning
confidence: 99%